Fray Luis y la poesía italiana, entre traducción e imitación. El caso de la canción de Giovanni della Casa - Elvezio Canonica (E-Spania)
After having reviewed the notions of imitation and translation based on the theoretical texts of Fray Luis, we propose a global table of all the poetic translations carried out by the Augustinian friar. Next, we focus on the analysis of a poetic translation from Italian, that of the song XXXII of Rimes by Giovanni della Casa (1558), which had not yet been studied. The result highlights the high quality of this translation, while showing the permeability of the theoretical boundaries between the notions of translation and imitation.